Cognitive Abilities of Visually Impaired Students in Relation to their Certain Demographic Variables - Sarkar/Bal, Puja (JOURNAL OF INDIAN EDUCATION, 2020)
The primary objective of this paper is to assess and compare the cognitive abilities of visually impaired students studying in Class VIII with regard to certain demographic variables. This study has covered three demographic variables namely gender, age of onset of visual impairment and students categorised on the basis of visual impairment. Data of the study were collected from ninety-one visually impaired students of Class VIII studying in special schools of Kolkata using two stage random sampling design. Indian adapted version of WISC-R (Verbal) for the visually impaired children developed and standardised by National Institute for Empowerment of Persons with Visual Disabilities (NIEPVD), Dehradun was used as a tool for data collection. The collected data was analysed with the help of statistical techniques like mean, SD and t value. The results of the statistical analysis revealed that there is a significant difference in the cognitive abilities between visually impaired boys and girls. It indicates that visually impaired boys are having relatively higher cognitive abilities than visually impaired girls. Furthermore, it was found that visually impaired student’s cognitive abilities did not differ significantly with respect to age of onset of blindness as well as to students categorised on the basis of visual impairment.